On the Integration of Roles in the UML - Depke, Ralph; Engels, Gregor; Küster, Jochen

Modeling Agent-Based Systems with Graph Transformation - Depke, Ralph; Heckel, Reiko; Küster, Jochen

On the Concurrent Semantics of Open Graph Transformation Systems and Views - Heckel, Reiko; Llabrés, Mercé; Ehrig, Hartmut; Orejas, Fernando

Ablaufvisualisierung für nebenläufige Java-Programme mit UML Interaktionsdiagrammen - Mehner, Katharina; Wagner, Annika

Ein Konzept zur anwendungsbezogenen UML-Semantikbeschreibung durch dynamische Metamodellierung - Hendrik Hausmann, Jan; Heckel, Reiko; Sauer, Stefan (Proceedings of the Workshop des Arbeitskreises GROOM der GI Fachgruppe 2.1.9 Objektorientierte Software-Entwicklung on Visuelle Verhaltensmodellierung verteilter und nebenläufiger Software-Systeme, Münster (Germany))
In diesem Beitrag stellen wir eine Methode zur Spezifikation der dynamischen Semantik von UML im Sinne einer Metamodellierung vor. Die dynamische Metamodellierung verwendet dabei UMLKollaborationsdiagramme als eine dem Modellierer bekannte Notation. Diese werden durch eine Interpretation als Regeln einer graphischen operationalen Semantik (GOS) semantisch präzisiert. Die GOS-Formalisierung beruht dabei sowohl auf Konzepten von Graphtransformationen als auch dem Ansatz der Structured Operational Semantics. GOS-Regeln werden als Deduktionsregeln für die Spezifikation eines Interpreters betrachtet, der basierend auf einer Prolog-Ausführungsmaschine realisert werden soll.

Modeling Agent-Based Systems with Graph Transformation and UML: From Requirement Specifcation to Object-Oriented Design - Depke, Ralph; Heckel, Reiko; Küster, Jochen (Proceedings of the workshop on Graph Transformation Systems (GraTra 2000), Berlin (Germany))

Concurrency of Double-Pullback Graph Transitions - Heckel, Reiko; Llabrés, Mercé; Ehrig, Hartmut; Orejas, Fernando (Proceedings of workshop on Graph Transformation Systems (GraTra; satellite event of the ETAPS 2000), Berlin (Germany))

A Framework for Adding Packages to Graph Transformation Approaches - Busatto, Giorgio; Engels, Gregor; Mehner, Katharina; Wagner, Annika (Selected Papers of the 6th International Workshop on Theory and Application of Graph Transformations (TAGT '98), Paderborn (Germany))
Graphs are a commonly used formalism for modeling many different kinds of static and dynamic data. In many applications, data modeling can be improved by using hierarchically structured graphs. But, while there already exist hierarchical graph data models, no general-purpose hierarchical graph data model exists yet, which unifies common features of these domain-specific models. In this paper, we present graph packages, a general formalism for defining hierarchical graphs, supporting the most important features found in known applications. Because of the dynamic nature of graphs, hierarchical graph transformation is also an important issue to be dealt with when using hierarchical graphs. Motivated by the successful application of graph grammars to the specification of graph transformations, we also introduce a framework that allows to specify hierarchical graph transformations by combining existing graph grammar approaches and our graph package concept. These concepts are a step towards the definition of a general-purpose hierarchical graph data model.

Graphical Operational Semantics - Corradini, Andrea; Heckel, Reiko; Montanari, Ugo (Proceedings of the Workshop on Graph Transformation and Visual Modelling Techniques (satellite event of the ICALP 2000), Geneva (Switzerland))

Towards Role-based Modeling of Autonomous Agents - Depke, Ralph; Heckel, Reiko (Proceedings of the Workshop des Arbeitskreises GROOM der GI Fachgruppe 2.1.9 Objektorientierte Software-Entwicklung on Visuelle Verhaltensmodellierung verteilter und nebenläufiger Software-Systeme, Münster (Germany))